2019
DOI: 10.1111/ors.12459
|View full text |Cite
|
Sign up to set email alerts
|

Osteoradionecrosis beyond the jaws: a mini case series and review of the literature

Abstract: Osteoradionecrosis (ORN) of the mandible is a well-known complication of head and neck radiotherapy (RT). In contrast, osteonecrosis of surrounding non-target structures in the craniofacial region is less commonly reported. Various bones within the head and neck are susceptible to ORN and this may present years after initial radiation exposure especially with improving survival rates. We report three cases of ORN involving the hyoid bone and temporal bone, and review the literature regarding numerous bones wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Worryingly, maxillofacial bones beyond the jaw have also been found to develop ORN even with IMRT. 30 RT dose is a well-recognised risk factor 10,31 and replicated in the current study (p = 0.007) particularly highlighting the OPC group in the 55-65 Gy and to a lesser degree the OCC group of the same dose. These finding align with those of Owosho et al 31 who found that 96% of ORN sites in their patients had been exposed to an average of 57.5 Gy while a number of studies highlighted the involvement of the jaws during RT delivery 28,29,[32][33][34] in this tumour group.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Worryingly, maxillofacial bones beyond the jaw have also been found to develop ORN even with IMRT. 30 RT dose is a well-recognised risk factor 10,31 and replicated in the current study (p = 0.007) particularly highlighting the OPC group in the 55-65 Gy and to a lesser degree the OCC group of the same dose. These finding align with those of Owosho et al 31 who found that 96% of ORN sites in their patients had been exposed to an average of 57.5 Gy while a number of studies highlighted the involvement of the jaws during RT delivery 28,29,[32][33][34] in this tumour group.…”
Section: Discussionsupporting
confidence: 76%
“…Interestingly, recent studies have shown that IMRT may in fact irradiate a larger area of the jaws 28,29 placing a wider span at risk of ORN. Worryingly, maxillofacial bones beyond the jaw have also been found to develop ORN even with IMRT 30 …”
Section: Discussionmentioning
confidence: 99%
“…18,19 It is argued that with IMRT all areas of the mouth become a target for some degree of exposure which explains the late effects not often seen previously. 20,21 Traditionally ORN has been associated maximum RT doses >60 to 75 Gy 6,15 ; however, it is now conceded that doses exceeding in the range of 30-40 Gy place patients at "at risk" of ORN. 22,23 There remains no international agreement on how to incorporate the predicted dose of radiation a dental unit will receive into the pre-treatment plan largely based upon the lack of knowledge at this level.…”
Section: Discussionmentioning
confidence: 99%
“… 5 Signs and symptoms of ORN include an area of exposed necrotic bone, numbness, abnormal mouth opening, orocutaneous fistula, and pain in the jaw area, which might also extend beyond the jaws. 8 Therefore, dental assessment before starting the treatment with radiotherapy for HNC patients is crucial. 9 This includes patient education about possible side effects of cancer therapy, prescription of a high fluoride-containing toothpaste, and dental extraction of teeth with a poor prognosis, which helps to reduce the need for dental extraction in HNC survivors post-radiotherapy, thereby reducing the risk of ORN.…”
Section: Introductionmentioning
confidence: 99%